Reactivity of TiO2 Nanotube‐Supported Platinum Particles in the CO Oxidation Reaction. Issue 4 (30th September 2016) - Krick Calderón, S.; Grabau, M.; Yoo, J. E.; Killian, M. S.; Schmuki, P.; Steinrück, H.‐P.; Papp, C.
Abstract: The CO oxidation on different platinum model catalysts, in particular differently sized Pt particles on vertically aligned TiO2 nanotubes ( d =80, l =200 nm) was investigated by near‐ambient‐pressure X‐ray photoelectron spectroscopy and simultaneous online gas analysis. The results are compared to the behavior on a TiO2 (1 1 0) rutile crystal with a similar Pt coverage and a Pt(1 1 1) single crystal. Temperature‐programmed reaction experiments at total pressures of 10 −3 to 1.0 mbar, and a CO/O2 ratio of 1:4 were performed to evaluate the reactivity of the samples. The onset temperature of the reaction on the Pt/TiO2 nanotube samples was found to be lower than on Pt(1 1 1) and Pt/TiO2 (1 1 0) and to decrease with decreasing particle size. For all particle samples, a steep increase in reaction rate at a defined temperature was observed, and at high temperatures the reaction became mass transfer‐limited in all cases. Isothermal measurements showed that no CO is adsorbed on the particles when CO oxidation has a high activity and metallic platinum is the active catalyst. Ageing of the TiO2 ‐supported samples is observed resulting in changes of the reaction onset and CO conversion. Abstract : Tubular Underground : The CO oxidation on differently sized Pt particles sputtered on vertically aligned TiO2 nanotubes is investigated. For all particle samples, a steep increase in reaction rate at a defined temperature is observed. At high temperatures the reaction becomes mass‐transfer limited.